2020
DOI: 10.3389/fmicb.2020.01017
|View full text |Cite
|
Sign up to set email alerts
|

Differentially Regulated Transcription Factors and ABC Transporters in a Mitochondrial Dynamics Mutant Can Alter Azole Susceptibility of Aspergillus fumigatus

Abstract: Azole resistance of the fungal pathogen Aspergillus fumigatus is an emerging problem. To identify novel mechanisms that could mediate azole resistance in A. fumigatus, we analyzed the transcriptome of a mitochondrial fission/fusion mutant that exhibits increased azole tolerance. Approximately 12% of the annotated genes are differentially regulated in this strain. This comprises upregulation of Cyp51A, the azole target structure, upregulation of ATP-binding cassette (ABC) superfamily and major facilitator super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 66 publications
1
12
1
Order By: Relevance
“…Overrepresentation of transmembrane transporter GOs, which indicates active transmembrane transport of a variety of substrates has been reported in many fungi [42,43]. Unlike the observed significant and specific enrichment of these GOs in glucose and xylose grown yeast observed in this study, genes associated with both GOs (GO:0022857 and GO:0055085) were reported to be up and downregulated on glucose grown Aspergillus fumigatus mutants [44]. To evaluate the potential implication of variation in the above differentially expressed sugar (and other) transporter genes during growth of the oleaginous yeast on xylose and glucose, we performed additional annotation of the predicted proteins using conserved domain database [36], the curated UniProtKB/Swiss-Prot [37] and transporter classification [38] databases as well as prediction of transmembrane helices using TMHMM Server v2.0 [39].…”
Section: Differential Gene Expression During Initial Growth Under Glucose and Xylose In Dsm 27192contrasting
confidence: 68%
See 1 more Smart Citation
“…Overrepresentation of transmembrane transporter GOs, which indicates active transmembrane transport of a variety of substrates has been reported in many fungi [42,43]. Unlike the observed significant and specific enrichment of these GOs in glucose and xylose grown yeast observed in this study, genes associated with both GOs (GO:0022857 and GO:0055085) were reported to be up and downregulated on glucose grown Aspergillus fumigatus mutants [44]. To evaluate the potential implication of variation in the above differentially expressed sugar (and other) transporter genes during growth of the oleaginous yeast on xylose and glucose, we performed additional annotation of the predicted proteins using conserved domain database [36], the curated UniProtKB/Swiss-Prot [37] and transporter classification [38] databases as well as prediction of transmembrane helices using TMHMM Server v2.0 [39].…”
Section: Differential Gene Expression During Initial Growth Under Glucose and Xylose In Dsm 27192contrasting
confidence: 68%
“…Overrepresentation of transmembrane transporter GOs, which indicates active transmembrane transport of a variety of substrates has been reported in many fungi [ 42 , 43 ]. Unlike the observed significant and specific enrichment of these GOs in glucose and xylose grown yeast observed in this study, genes associated with both GOs (GO:0022857 and GO:0055085) were reported to be up and downregulated on glucose grown Aspergillus fumigatus mutants [ 44 ].…”
Section: Resultsmentioning
confidence: 77%
“…Although mitochondrial fission is related to increased azole resistance, the molecular mechanism underlying the increased azole resistance is still unclear. One possible mechanism in A. fumigatus is that mitochondrial fission defects lead to a decrease in intracellular azole drug concentration through upregulating multiple efflux pumps ( Figure 2 ) [ 41 ], dampening the inhibition of lanosterol 14α demethylase (Cyp51A) by azole drugs. Recently, an important contribution of mitochondrial fission to azole susceptibility of C. albicans has been reported.…”
Section: Role Of Fungal Mitochondria In Azole Resistancementioning
confidence: 99%
“…Moreover, the subsequent signal pathway enrichment analysis performed using the Kyoto Encyclopedia of Genes and Genomes (KEGG) database showed that the aforementioned differentially expressed genes were mainly mapped to metabolic processes. Of them, ATP-binding cassette (ABC) transporters ( Figure 4C ), a type of fungal drug efflux pumps (Sturm et al, 2020 ), were enriched, suggesting that gemA deletion may be affected by intracellular drug residues in the fungus. In addition, as shown in Figure 4D , the selected genes, including those encoding the ABC transporters and major facilitators superfamily (MFS, another type of drug efflux pump), were broadly upregulated in the Δ gemA mutant compared with the WT strain.…”
Section: Resultsmentioning
confidence: 99%